High density polyethylene resin composition for secondary battery separators with high strength and shut down property, porous separator using the same and preparing method of the same
A high-density polyethylene resin composition with specific molecular weight and melting point ranges, combined with solvent extraction, addresses the challenge of achieving high strength and shutdown characteristics in thin secondary battery separators, resulting in improved safety and energy density.
Patent Information
- Application Number
- KR1020240167479
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2044-11-21
AI Technical Summary
Existing secondary battery separators face challenges in achieving high strength and effective shutdown characteristics at thin thicknesses, particularly with the use of high-density polyethylene with molecular weights between 900,000 and 1.2 million, which are not sufficient to meet the requirements for safety and energy density.
A high-density polyethylene resin composition comprising high-molecular-weight and low-melting-point polyethylene with specific molecular weight and melting point ranges, combined with a liquid low-molecular-weight material, is used to form a porous separator through extrusion, stretching, and solvent extraction to create a membrane with improved strength and shutdown characteristics.
The resulting porous separator exhibits excellent air permeability, puncture strength, and shutdown characteristics, maintaining these properties at a thin thickness of 4 to 6 μm, enhancing safety and energy density.
Smart Images

Figure 112024128534733-PAT00001
Abstract
Description
Technology Field
[0001] The present invention relates to a porous separator for a secondary battery and a method for manufacturing the same, and more specifically, to a high-density polyethylene resin composition for a secondary battery separator and a porous separator for a secondary battery with improved strength and shutdown characteristics using the same and a method for manufacturing the same. Background Technology
[0002] Since the commercialization of lithium secondary batteries, the development of new separators has continued, exhibiting excellent mechanical and electrical properties and ensuring safety such as shutdown and meltdown characteristics.
[0003] Currently, microporous separators using polyolefin-based materials form the mainstream for lithium-ion battery separators. As electric vehicles become increasingly widespread, battery safety is becoming a critical issue due to concerns such as battery fires. Therefore, it is essential to develop separators with a low shutdown temperature to prevent battery overcharging and thermal runaway by blocking the movement of lithium ions by sealing pores in advance when the battery temperature rises. Furthermore, there is a growing trend of using separators with a thickness of 7 to 9 µm to maximize energy density, and several battery manufacturers are currently evaluating the performance of batteries using 5 µm prototype separators and are gradually proceeding with commercialization.
[0004] Meanwhile, wet separators for secondary batteries have conventionally used high-density polyethylene with a weight-average molecular weight of 400,000 to 600,000. Recently, to increase the energy density of secondary batteries, high-density polyethylene with a weight-average molecular weight between 900,000 and 1.2 million is being used as a thinner separator, but it is not easy to satisfy the high strength required when using ultra-thin separators.
[0005] Therefore, there is a need to develop a porous separator for secondary batteries using high-density polyethylene with a weight-average molecular weight of 2 million, which improves high strength and shutdown characteristics even at a thin thickness of 4 to 6 μm.
[0006] Korean Published Patent No. 2006-0118135 has a weight-average molecular weight of 2×10 5 ~4×10 5 and the molecular weight is 1×10 4 The content of molecules below 5% by weight and simultaneously 1×10 6 A microporous membrane composed of high-density polyethylene having a molecular content of 5% by weight or less is disclosed, but it is difficult to realize a high-strength porous separation membrane because the molecular weight is too low. The problem to be solved
[0007] The present invention aims to provide high-density polyethylene for secondary battery separators and porous separators for secondary batteries using the same, wherein high-molecular-weight high-density polyethylene with improved high strength characteristics and excellent shutdown characteristics even at a thin thickness, porous separators for secondary batteries using the same, and a method for manufacturing the same. means of solving the problem
[0008] To solve the above problem, the present invention provides a high-density polyethylene resin composition for a secondary battery separator comprising: 60 to 85 parts by weight of high-molecular-weight high-density polyethylene having a weight-average molecular weight of 1,800,000 to 2,500,000 g / mol and a melting point of 131 to 135°C; and 15 to 40 parts by weight of low-melting-point low-molecular-weight high-density polyethylene having a weight-average molecular weight of 200,000 to 400,000 g / mol, a melting point of 122 to 127°C, and a high molecular weight content of 5 to 15% by weight of ultra-low molecular weight with a molecular weight of 10,000 g / mol or less.
[0009] To solve the above additional problem, the present invention provides a porous separator for a secondary battery comprising the high-density polyethylene resin composition.
[0010] In addition, the above-described separator provides a porous separator for a secondary battery characterized by having a thickness of 4 to 6 μm.
[0011] In addition, the above-described separator provides a porous separator for a secondary battery characterized by having an air permeability of 80 to 150 s / 100cc, a perforation strength of 350 to 500 gf, and a closed-hole temperature of 130 to 140℃ as measured by the following method.
[0012] [Method for Measuring Air Permeability]
[0013] The time taken for 100 cc of air to pass through a circular specimen with a thickness of 4 to 6 μm and a diameter of 1 inch was measured at a pressure of 6.52 psi;
[0014] [Method for Measuring Drilling Strength]
[0015] After cutting a separator membrane with a thickness of 4 to 5 μm into a size of 50 × 50 mm, placing the specimen on a plate with a 10 mm diameter hole and fixing it, the force at the point where the specimen is pierced is measured when a 1 mm diameter (radius of curvature 0.5 mm) probe is lowered at a speed of 0.05 cm / sec;
[0016] [Method for Measuring Abandoned Air Temperature]
[0017] In a convection oven capable of increasing the temperature, the membrane used for measuring the perforation strength is heated from 130°C in increments of 1°C until the pores of the membrane melt and the air permeability is measured at a temperature of 500 s / 100cc or more.
[0018] To solve the above-mentioned other problem, the present invention comprises: (a) a step of forming a sheet by extruding a composition comprising: 60 to 85 parts by weight of high-molecular-weight high-density polyethylene having a weight-average molecular weight of 1,800,000 to 2,500,000 g / mol and a melting point of 131 to 135°C; 15 to 40 parts by weight of low-melting-point low-molecular-weight high-density polyethylene having a weight-average molecular weight of 200,000 to 400,000 g / mol, a melting point of 122 to 127°C, and a high molecular weight content of 5 to 15% by weight of ultra-low molecular weight with a molecular weight of 10,000 g / mol or less; and 250 to 350 parts by weight of a liquid low molecular weight material; (b) a step of stretching the extruded sheet; and (c) a step of extracting and removing the liquid low-molecular-weight substance from the stretched sheet using an extraction solvent; a method for manufacturing a porous separator for a secondary battery is provided.
[0019] In addition, a method for manufacturing a porous separator for a secondary battery is provided, characterized in that in step (a) above, the liquid low molecular weight material is one or more selected from the group consisting of aliphatic hydrocarbon compounds, vegetable oils, and phthalate-based materials.
[0020] In addition, the method for manufacturing a porous separator for a secondary battery is characterized in that in step (b), the sheet formed in step (a) is stretched 6 to 15 times in the longitudinal direction (MD) and transverse direction (TD), respectively, at 100 to 130°C, and in step (c), the extraction solvent is one or more selected from the group consisting of methylene chloride, ethanol, and methanol, and the liquid low molecular weight material is removed to form pores. Effects of the invention
[0021] The present invention provides a porous separator for a secondary battery, which is manufactured by extracting and removing a liquid low-molecular-weight substance from a sheet formed from a composition comprising high-density polyethylene and a liquid low-molecular-weight substance, wherein a high-molecular-weight high-density polyethylene having a specific range of molecular weight and melting point and a low-melting-point low-molecular-weight high-density polyethylene having a specific range of molecular weight, melting point and ultra-low molecular weight are mixed and used to provide a high-density polyethylene resin composition for a secondary battery separator that has excellent air permeability and improved high strength and shutdown characteristics even at a thin thickness, a porous separator for a secondary battery using the same, and a method for manufacturing the same. Specific details for implementing the invention
[0022] The present invention will be described in detail below through preferred embodiments. Prior to this, terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings. Instead, based on the principle that the inventor may appropriately define the concepts of terms to best describe their invention, they should be interpreted in a meaning and concept consistent with the technical spirit of the present invention. Therefore, the configurations of the embodiments described in this specification are merely the most preferred embodiments of the present invention and do not represent all aspects of the technical spirit of the present invention; thus, it should be understood that various equivalents and modifications capable of replacing them may exist at the time of filing this application.
[0024] The present invention discloses a high-density polyethylene resin composition for a secondary battery separator comprising: 60 to 85 parts by weight of high-molecular-weight high-density polyethylene having a weight-average molecular weight of 1,800,000 to 2,500,000 g / mol and a melting point of 131 to 135°C; and 15 to 40 parts by weight of low-melting-point low-molecular-weight high-density polyethylene having a weight-average molecular weight of 200,000 to 400,000 g / mol, a melting point of 122 to 127°C, and a high molecular weight content of 5 to 15% by weight of ultra-low molecular weight with a molecular weight of 10,000 g / mol or less. The invention also discloses a porous separator for a secondary battery comprising the high-density polyethylene resin composition. In this case, the porous separator is formed by extracting and removing the liquid low-molecular-weight material from a sheet formed from a composition comprising the high-density polyethylene resin composition and a liquid low-molecular-weight material, thereby forming pores.
[0025] The above-mentioned liquid low-molecular-weight material is a liquid organic material having a molecular structure similar to polyethylene, and can form a thermodynamically homogeneous single phase with polyethylene at high temperatures. When the solution of polyethylene and the liquid organic material, which has formed a single phase at high temperatures in this way, is cooled from high temperature to room temperature, phase separation occurs between the polyethylene and the liquid organic material. Phase separation can proceed in different forms depending on the cooling rate, but typically, it separates into a polymer-rich phase, which is the crystalline portion of polyethylene, and a polymer-lean phase, which is the liquid portion. After cooling, if the polymer-lean phase is removed through an extraction process with an organic solvent, a porous polyethylene membrane with overall pores can be manufactured. The porous structure of the membrane formed in this way is determined during the phase separation process, and the size and crystal structure of the polymer-rich phase and the polymer-lean phase determine the pore size and structure of the final membrane.
[0026] In the present invention, the high molecular weight high-density polyethylene has a weight-average molecular weight of 1,800,000 to 2,500,000 g / mol and a melting point of 131 to 135℃. If the weight-average molecular weight of the high molecular weight high-density polyethylene is less than 1,800,000 g / mol, the long chains of the polymer fail to uniformly connect and fix the inter-lamellar clusters of the crystal during thin film forming, resulting in reduced puncture strength; if the weight-average molecular weight exceeds 2,500,000 g / mol, the polyethylene and the liquid low molecular weight organic material are not homogeneously mixed on the extruder, causing gel formation and poor flowability of the solution, which leads to melt fracture during membrane forming. In addition, if the melting point of the high molecular weight high-density polyethylene is less than 131°C, the crystallization rate during the manufacture of the separation membrane is too low, so pores are not formed uniformly, and the air permeability is reduced.
[0027] In addition, in the present invention, the low-melting point low-molecular-weight high-density polyethylene has a weight-average molecular weight of 200,000 to 400,000 g / mol, a melting point of 122 to 127°C, and an ultra-low molecular weight content of 5 to 15 weight% with a molecular weight of 10,000 g / mol or less. When the weight-average molecular weight of the low-melting point low-molecular-weight high-density polyethylene is less than 200,000 g / mol, the ultra-low molecular weight content increases, and the ultra-low molecular weight itself acts as a defect during membrane molding, thereby reducing the puncture strength. When the weight-average molecular weight exceeds 400,000 g / mol, the ultra-low molecular weight has the characteristic of closing pores due to high fluidity (low viscosity) at high temperatures, and as this ultra-low molecular weight content becomes too low, the pore closing temperature of the membrane increases, and the shutdown characteristics are reduced. In addition, if the melting point of the above low-melting-point, low-molecular-weight high-density polyethylene is less than 122°C, the pores become clogged during high-temperature stretching in the membrane manufacturing process, resulting in reduced air permeability; if the melting point exceeds 127°C, the closed-pore temperature of the membrane increases, leading to a decrease in shutdown characteristics. Furthermore, if the ultra-low molecular weight content of 10,000 g / mol or less is less than 5% by weight, the closed-pore temperature increases, leading to a decrease in shutdown characteristics; and if the content exceeds 15% by weight, the puncture strength decreases.
[0028] In the present invention, the mixing ratio of the high molecular weight high-density polyethylene and the low melting point low molecular weight high-density polyethylene is 60 to 85 parts by weight and 15 to 40 parts by weight, respectively, preferably 70 to 85 parts by weight and 15 to 30 parts by weight, respectively, and more preferably 75 to 85 parts by weight and 15 to 25 parts by weight, respectively. If the content of the high molecular weight high-density polyethylene is excessive or the content of the low melting point low molecular weight high-density polyethylene does not reach a certain level, the ratio of high molecular weight and high melting point resins increases, resulting in slightly reduced air permeability and increased closed hole temperature, which lowers shutdown characteristics; and if the content of the low melting point low molecular weight high-density polyethylene is excessive or the content of the high molecular weight high-density polyethylene does not reach a certain level, the ratio of low molecular weight and low melting point resins increases, resulting in reduced puncture strength.
[0029] In this way, the present invention provides a porous separator for a secondary battery that is manufactured by extracting and removing a liquid low-molecular-weight material from a sheet formed from a composition comprising high-density polyethylene and a liquid low-molecular-weight material, wherein a high-molecular-weight high-density polyethylene having a specific range of molecular weight and melting point and a low-melting-point low-molecular-weight high-density polyethylene having a specific range of molecular weight, melting point and ultra-low molecular weight can be mixed to provide a porous separator for a secondary battery that has excellent air permeability and improved high strength and shutdown characteristics even at a thin thickness.
[0030] Specifically, the porous separator for a secondary battery according to the present invention may have an air permeability of 80 to 150 s / 100cc, preferably 80 to 135 s / 100cc, measured by the following measurement method, a puncture strength of 350 to 500 gf, and a closed pore temperature of 130 to 140℃.
[0031] [Method for Measuring Air Permeability]
[0032] The time taken for 100 cc of air to pass through a circular specimen with a thickness of 4 to 5 μm and a diameter of 1 inch was measured at a pressure of 6.52 psi;
[0033] [Method for Measuring Drilling Strength]
[0034] After cutting a separator membrane with a thickness of 4 to 5 μm into a size of 50 × 50 mm, placing the specimen on a plate with a 10 mm diameter hole and fixing it, the force at the point where the specimen is pierced is measured when a 1 mm diameter (radius of curvature 0.5 mm) probe is lowered at a speed of 0.05 cm / sec;
[0035] [Method for Measuring Abandoned Air Temperature]
[0036] In a convection oven capable of increasing the temperature, the membrane used for measuring the perforation strength is heated from 130°C in increments of 1°C until the pores of the membrane melt and the air permeability is measured at a temperature of 500 s / 100cc or more.
[0037] Hereinafter, a method for manufacturing a porous separator for a secondary battery according to the present invention will be described in detail.
[0038] A method for manufacturing a porous separator for a secondary battery according to the present invention comprises: (a) a step of forming a sheet by extruding a composition comprising: 60 to 85 parts by weight of high-molecular-weight high-density polyethylene having a weight-average molecular weight of 1,800,000 to 2,500,000 g / mol and a melting point of 131 to 135°C; 15 to 40 parts by weight of low-melting-point low-molecular-weight high-density polyethylene having a weight-average molecular weight of 200,000 to 400,000 g / mol, a melting point of 122 to 127°C, and a high molecular weight content of 5 to 15% by weight of ultra-low molecular weight with a molecular weight of 10,000 g / mol or less; and 250 to 350 parts by weight of a liquid low molecular weight material; (b) a step of stretching the extruded sheet; and (c) a step of extracting and removing the liquid low molecular weight material from the stretched sheet using an extraction solvent.
[0039] Step (a) above is a step of mixing a high-density polyethylene resin composition and a liquid low-molecular-weight material for manufacturing a wet porous separation membrane, and the mixing process is not particularly limited as long as it is extruded into a sheet form.
[0040] In the present invention, the high molecular weight high-density polyethylene is a resin composition used considering the physical properties and heat resistance of the porous separation membrane, and may be 0.940 to 0.960 g / cm³. In addition, the density of the low melting point low molecular weight high-density polyethylene may be 0.920 to 0.960 g / cm³.
[0041] In the present invention, the mixing process can be performed, for example, by placing the high molecular weight high-density polyethylene, the low melting point low molecular weight high-density polyethylene, and the liquid low molecular weight material into a twin-screw extruder at 220 to 240°C at a speed of 40 to 80 rpm, and if prevention of yellowing is required, the mixing process can be performed after adding a neutralizing agent, an antioxidant, etc.
[0042] In the above mixing process, the extruded material is formed into a sheet shape by a casting method using a T-die. At this time, the temperature of the die may be 200 to 250°C, and the temperature of the cooling roll may be 10 to 60°C. If the temperature of the cooling roll is too high, the crystal size increases during phase separation, reducing the elongation and causing the sheet to break during stretching; if the temperature of the cooling roll is too low, the crystal size becomes too small and dense, which may reduce the porosity of the separator.
[0043] The above liquid low-molecular-weight material may be in the form of a single substance or a mixture of two or more liquid substances, and is not particularly limited as long as it is a substance that can be used to form pores in a polyethylene membrane, and which can form pores by being mixed with polyethylene at high temperature to form a single phase, then undergoing phase separation upon cooling, and being removed by an extraction solvent. For example, aliphatic hydrocarbon compounds such as paraffin oil, vegetable oils, phthalate-based substances, etc., may be used, and preferably, liquid paraffin oil that has good compatibility with polyethylene and is harmless may be used.
[0044] In the present invention, the content of the liquid low-molecular-weight material mixed with the high molecular weight high-density polyethylene and the low melting point low molecular weight high-density polyethylene is 250 to 350 parts by weight based on the relative weight with respect to them, preferably 260 to 340 parts by weight, and more preferably 270 to 330 parts by weight. If the content of the liquid low-molecular-weight material is too high, the porosity of the separation membrane becomes excessive, and the perforation strength decreases; if the content is too low, the porosity decreases, and the air permeability decreases.
[0045] Step (b) above is a sheet forming step using a stretching machine, and the stretching of the extruded sheet can be performed using a biaxial stretching machine. The temperature during stretching may be 100 to 130°C, preferably 110 to 120°C, and the stretching may be performed by stretching the sheet 6 to 15 times in the longitudinal (MD) direction and 9 to 12 times in the transverse direction, respectively.
[0046] If the temperature during stretching is less than 100℃, the load increases during stretching, which may cause slippage of the clips fixing the sheet, and the increased strength of the sheet may result in incomplete stretching and breakage. Additionally, if the temperature during stretching exceeds 130℃, the pore portions may melt during stretching, preventing the formation of pores. Furthermore, if the stretching ratio is less than 6 times in the longitudinal and transverse directions, it may be difficult to manufacture a separator with a thickness of 5 μm, and pores may not be properly formed. If the stretching ratio exceeds 15 times in the longitudinal and transverse directions, the sheet may tear during the stretching process, making it unusable as a separator.
[0047] Step (c) above is a step in which pores are formed in the sheet, specifically, the liquid low-molecular-weight material is removed from the sheet stretched in step (b) to form pores. The porosity of the polyethylene porous separator with formed pores may be, for example, 40 to 60%, and preferably 45 to 55%.
[0048] To extract the above liquid low molecular weight substance, an organic solvent that is compatible with the liquid low molecular weight substance may be used, for example, methylene chloride, ethanol, methanol, etc. may be used, and preferably, methylene chloride may be used.
[0049] In the present invention, a step of removing residual stress of the sheet after step (c) may be further performed. That is, the present invention may further include a step of (d) heat-setting the extracted sheet at 100 to 140°C after fixing it.
[0050] Step (d) above involves a heat-setting step to remove residual stress and reduce the shrinkage rate of the final sheet. Heat-setting is performed by fixing the sheet and applying heat, thereby forcibly holding the sheet intended to shrink to remove residual stress. The heat-setting temperature may be 100 to 140°C, preferably 110 to 130°C. A higher heat-setting temperature is advantageous for reducing the shrinkage rate, but if the temperature exceeds a certain level, the pores may partially melt, leading to a decrease in porosity. The heat-setting time should be relatively short when the heat-setting temperature is high, and conversely, relatively long when the heat-setting temperature is low; specifically, the heat-setting time is preferably about 1 to 5 minutes.
[0051] Meanwhile, regarding separator thickness, since the ionic conductivity of organic liquid electrolytes is generally about 100 times lower than that of aqueous electrolytes, it is important to increase the reaction surface area of the electrodes while reducing the distance between electrode plates to achieve high power output and high energy density of the battery. Therefore, in terms of battery resistance, the thickness of the separator should not exceed 25 µm. In practice, separators with a thickness of 10 to 20 µm are widely used, and depending on the type of battery, separators with a thickness of 10 µm or less are also used. Using a thin separator increases the discharge capacity of the electrodes because electrolyte movement is promoted as the separator thickness decreases. However, as the separator becomes thinner, the puncture strength decreases, making it prone to pinholes or tearing, and the likelihood of short circuits between electrodes increases, which can reduce safety.
[0052] In addition, the puncture strength of the separator represents resistance to risks that may arise due to foreign substances that may be incorporated during electrode formation, the surface conditions of the anode and cathode, and lithium dendrites. Typically, a drill of a certain size is mounted on a tensile testing machine, and while the separator is held taut in the holder to prevent relaxation, the drill is dropped onto the separator at a constant speed to measure and verify the fracture strength. At this time, a stress-strain curve is obtained, the maximum value is set as the puncture strength, and the area under the curve is evaluated as the strain energy.
[0053] It is known that, typically, the puncture strength of a separator for a secondary battery is required to be at least 300 gf, and preferably at least 350 gf, to prevent pinholes and short circuits in the separator. This puncture strength of the separator is a property that depends significantly on the separator material and the manufacturing process. High polymer entanglement and high elongation enable excellent puncture strength of the separation membrane. In the present invention, high-density polyethylene having a weight-average molecular weight of 1.8 million to 2.5 million is used as a material, and high-density polyethylene having a melting point within a specific range is used, and high-density polyethylene having a low melting point and low molecular weight having a specific range of molecular weight, melting point, and ultra-low molecular weight is mixed and a high elongation ratio is applied, thereby enabling the manufacture of an ultra-thin, high-strength separation membrane with improved air permeability and excellent puncture strength, effectively lowering the closed-hole temperature and improving shutdown characteristics in the separation membrane material, even at a thin separation membrane thickness of 5 μm, specifically 4 to 6 μm, preferably 4.5 to 5.5 μm.
[0054] Specific embodiments according to the present invention will be described below.
[0056] Examples 1 to 4, Comparative Examples 1 to 9
[0057] High molecular weight high-density polyethylene having a weight-average molecular weight (Mw) and melting point (Tm) as listed in Table 1 below and a density of about 0.950 g / cm³; low melting point low molecular weight high-density polyethylene having a weight-average molecular weight (Mw), molecular weight distribution (MWD, Mw / Mn), ultra-low molecular weight content of 10,000 g / mol or less and a melting point (Tm) as listed in Table 1 below and a density of about 0.940 g / cm³; and liquid paraffin oil (kinematic viscosity of 66 to 70 cSt at 40°C, density of about 0.857 g / cc) as a low molecular weight organic material were each fed into a twin-screw extruder at a ratio of 300 parts by weight to a total of 100 parts by weight of the two types of high-density polyethylene, and a sheet was formed by extruding and casting into a T-die under twin-screw extruder temperature conditions of 230°C. At this time, the temperature of the cooling roll during casting was set to 20°C. The molded extruded sheet was stretched 10 times in the longitudinal direction (MD) and 12 times in the transverse direction (TD) using a biaxial stretcher under a stretching temperature of 115°C. The stretched sheet was fixed to a jig to prevent shrinkage, and low molecular weight organic material was extracted using methylene chloride as an extraction solvent. Afterward, the sheet was heat-set at 125°C to produce a porous separation membrane (porosity 45 to 50%) with the thickness listed in Table 1 below. The molecular weight characteristics of each high-density polyethylene were measured using a high-temperature Gel Permeation Chromatography (GPC) from Agilent Technologies.
[0059] Experimental Example
[0060] For the porous membranes prepared in the above examples and comparative examples, air permeability, puncture strength, and closed-hole temperature were measured according to the following method, and the results are shown in Table 1 below.
[0061] [Method for Measuring Air Permeability]
[0062] For a circular specimen with a diameter of 1 inch made of the above-manufactured membrane, the time taken for 100 cc of air to pass through at a pressure of 6.52 psi was measured, and the average value was calculated by excluding the maximum and minimum values after 5 measurements.
[0063] [Method for Measuring Drilling Strength]
[0064] After cutting the above-manufactured separator into 50 × 50 mm pieces, the specimen was placed on a plate with a 10 mm diameter hole and fixed. Then, the force at which the specimen was pierced was measured by lowering a 1 mm diameter (0.5 mm radius of curvature) probe at a speed of 0.05 cm / sec, and the measurement was taken 5 times and calculated as the average value.
[0065] [Method for Measuring Abandoned Air Temperature]
[0066] In a convection oven capable of increasing the temperature from 130℃ to 200℃, the used separator prepared above was heated in increments of 1℃ starting from 130℃, and the temperature was measured at which the pores of the separator melted and the air permeability became 500 s / 100cc or more.
[0068]
[0071] Referring to Table 1, in a porous separator for a secondary battery manufactured by extracting and removing the liquid low-molecular-weight material from a sheet formed from a composition comprising high-density polyethylene and a liquid low-molecular-weight material, when high-molecular-weight high-density polyethylene having a specific range of molecular weight and melting point and high-density polyethylene having a specific range of molecular weight, melting point and ultra-low molecular weight are mixed and used according to the present invention (Examples 1 to 4), it is confirmed that excellent permeability is maintained at a level of 130 s / 100cc or less, while exhibiting a puncture strength of 350 gf or more, and in particular, a closed hole temperature of 140℃ or less, so that excellent shutdown characteristics can be realized along with high strength characteristics even at a thin thickness.
[0072] In this regard, it can be seen that if the high molecular weight high-density polyethylene content is excessive (Comparative Example 1) or the melting point does not reach a certain level (Comparative Example 4), the air permeability decreases and the closed hole temperature increases, thereby reducing the shutdown characteristics, and if the content does not reach a certain level (Comparative Example 2), the puncture strength decreases.
[0073] In addition, it can be seen that if the weight-average molecular weight of high-density polyethylene does not fall within a certain range (Comparative Example 3), the puncture strength decreases, and if it exceeds that range (Comparative Example 6), melt fracture occurs during membrane molding.
[0074] In addition, it can be seen that in low-melting-point, low-molecular-weight high-density polyethylene, when the ultra-low molecular weight content of 10,000 g / mol or less is excessive (Comparative Example 5), the puncture strength decreases, and when the content does not reach a certain level and the weight-average molecular weight is somewhat high (Comparative Example 7), the puncture temperature increases and the shutdown characteristics decrease.
[0075] In addition, it can be seen that if the melting point of low-melting-point, low-molecular-weight high-density polyethylene does not reach a certain level (Comparative Example 8), the air permeability decreases, and if the melting point is excessively high (Comparative Example 9), the closed air temperature increases and the shutdown characteristics decrease.
[0077] Preferred embodiments of the present invention have been described in detail above. The description of the present invention is for illustrative purposes only, and those skilled in the art will understand that other specific forms can be easily modified without changing the technical concept or essential features of the present invention.
[0078] Accordingly, the scope of the present invention is defined by the claims set forth below rather than by the detailed description above, and all modifications or variations derived from the meaning, scope, and equivalent concepts of the claims should be interpreted as being included within the scope of the present invention.
Claims
Claim 1 A high-density polyethylene resin composition for a secondary battery separator comprising: 60 to 85 parts by weight of high-molecular-weight high-density polyethylene having a weight-average molecular weight of 1,800,000 to 2,500,000 g / mol and a melting point of 131 to 135°C; and 15 to 40 parts by weight of low-melting-point low-molecular-weight high-density polyethylene having a weight-average molecular weight of 200,000 to 400,000 g / mol, a melting point of 122 to 127°C, and an ultra-low molecular weight content of 5 to 15% by weight with a molecular weight of 10,000 g / mol or less. Claim 2 A porous separator for a secondary battery comprising the high-density polyethylene resin composition of claim 1. Claim 3 A porous separator for a secondary battery according to claim 2, characterized in that the separator has a thickness of 4 to 6 μm. Claim 4 A porous separator for a secondary battery according to claim 3, characterized in that the separator has an air permeability of 80 to 150 s / 100cc, a puncture strength of 350 to 500 gf, and a closed hole temperature of 130 to 140℃ as measured by the following method: [Method for measuring air permeability] Measuring the time required for 100 cc of air to permeate through a circular specimen with a thickness of 4 to 6 μm and a diameter of 1 inch at a pressure of 6.52 psi; [Method for measuring puncture strength] After cutting a separator with a thickness of 4 to 5 μm into a size of 50 × 50 mm, placing the specimen on a plate with a hole of 10 mm in diameter and fixing it, and then measuring the force at the point where the specimen is punctured when a probe with a diameter of 1 mm (radius of curvature of 0.5 mm) is lowered at a speed of 0.05 cm / sec; [Method for measuring closed hole temperature] In a convection oven capable of raising the temperature, the above The membrane used for measuring puncture strength was heated from 130°C in increments of 1°C until the pores of the membrane melted and the air permeability became 500 s / 100cc or higher. Claim 5 (a) a step of forming a sheet by extruding a composition comprising: 60 to 85 parts by weight of high-molecular-weight high-density polyethylene having a weight-average molecular weight of 1,800,000 to 2,500,000 g / mol and a melting point of 131 to 135°C; 15 to 40 parts by weight of low-melting-point low-molecular-weight high-density polyethylene having a weight-average molecular weight of 200,000 to 400,000 g / mol, a melting point of 122 to 127°C, and an ultra-low molecular weight content of 5 to 15% by weight with a molecular weight of 10,000 g / mol or less; and 250 to 350 parts by weight of a liquid low molecular weight material; (b) a step of stretching the extruded sheet; and (c) a step of extracting and removing the liquid low molecular weight material from the stretched sheet using an extraction solvent; comprising a method for manufacturing a porous separator for a secondary battery. Claim 6 A method for manufacturing a porous separator for a secondary battery according to claim 5, wherein in step (a) above, the liquid low molecular weight material is one or more selected from the group consisting of aliphatic hydrocarbon compounds, vegetable oils, and phthalate-based materials. Claim 7 A method for manufacturing a porous separator for a secondary battery according to claim 5, wherein in step (b), the stretching is performed by stretching the sheet formed in step (a) 6 to 15 times in the longitudinal direction (MD) and transverse direction (TD), respectively, at 100 to 130°C, and in step (c), the extraction solvent is one or more selected from the group consisting of methylene chloride, ethanol, and methanol, and the liquid low molecular weight material is removed to form pores.
Citation Information
Patent Citations
Low-closed-cell and high-rupture polyethylene lithium battery diaphragm and preparation method thereof
CN113745756A
Polyethylene microporous membrane and its manufacturing method
JP2001200082A
Polyolefin composite porous membrane and method for producing the same, and battery separator and battery
KR1020200085746A
